ASSOCIATION OF WRITING AND MOTRICITY IN EARLY SCHOOL CHILDREN (Fiep Bulletin - online, 2025)
Introduction: The development of motor skills is a process in which it has been increasingly correlated with the acquisition of writing as it is related to maturational cognitive aspects in general. Objective: Assess motor development: fine motor skills, global motor skills, balance, body scheme/speed, spatial organization, language/temporal organization, laterality and associate with learning to write. Methods: Cross-sectional and descriptive research whose sample consisted of 58 children aged 3 to 6 in a public school in Teresina-PI. A demographic questionnaire, the Rosa Neto Motor Development Scale (2002) and the adapted test from Helena Serra (2005) were used to collect data to assess writing. The BoxPlot descriptive statistics contributed to analyzing descriptive data and the Kruskal-Wallis and Chi-square tests inferential data. Results: Serious associations were identified between IMG and writing (p>0.0001) as well as fine motor skills (p>0.001), global motor skills (p>0.001), balance (p>0.007), body layout (p>0.001), spatial organization (p>0.001) and temporal organization (p>0.001) and writing. It was shown that children at level 2 did not present difficulties in writing and were the ones who presented more symmetrical data, demonstrating that writing and motor skills were more involved. Conclusion: The group of children who did not compromise in writing are children with more developed motor skills.
Keywords: Physical Education; motor dexterity; handwriting; preschool education